Where Play and Poetic Word Meet as a Generation Device: a few Reflections - Lepri, Chiara (Studi sulla Formazione/Open Journal of Education, 2017)
There is a link between the experience of the Anglo-Saxon nonsense by Lear and Carroll, literary surrealist experimentation, and poetry for children by Rodari onwards. Word becomes playful and close to feeling childish: one could say that it mimics a primitive language that pursues more phonetic associations rather than sense, until it generates semantic disorientation and surprise, as well as comedy and entertainment through the transgression of formally shared codes. Word thus conceived (and played, using various reconstruction and decomposition techniques) takes on an extraordinary poietic power and encourages interpretative work of an ever new reality.